Efficient spiral in‐out and EPI balanced steady‐state free precession cine imaging using a high‐performance 0.55T MRI. Issue 5 (14th April 2020) - Restivo, Matthew C.; Ramasawmy, Rajiv; Bandettini, W. Patricia; Herzka, Daniel A.; Campbell‐Washburn, Adrienne E.
Abstract : Purpose: Low‐field MRI offers favorable physical properties for SNR‐efficient long readout acquisitions such as spiral and EPI. We used a 0.55 tesla (T) MRI system equipped with high‐performance hardware to increase the sampling duty cycle and extend the TR of balanced steady‐state free precession (bSSFP) cardiac cine acquisitions, which typically are limited by banding artifacts. Methods: We developed a high‐efficiency spiral in‐out bSSFP acquisition, with zeroth‐ and first‐gradient moment nulling, and an EPI bSSFP acquisition for cardiac cine imaging using a contemporary MRI system modified to operate at 0.55T. Spiral in‐out and EPI bSSFP cine protocols, with TR = 8 ms, were designed to maintain both spatiotemporal resolution and breath‐hold length. Simulations, phantom imaging, and healthy volunteer imaging studies ( n = 12) were performed to assess SNR and image quality using these high sampling duty‐cycle bSSFP sequences. Results: Spiral in‐out bSSFP performed favorably at 0.55T and generated good image quality, whereas EPI bSSFP suffered motion and flow artifacts. There was no difference in ejection fraction comparing spiral in‐out with standard Cartesian imaging. Moreover, human images demonstrated a 79% ± 21% increase in myocardial SNR using spiral in‐out bSSFP and 50% ± 14% increase in SNR using EPI bSSFP as compared with the reference Cartesian acquisition. Spiral in‐out acquisitions at 0.55T recovered 69% ± 14% of the myocardial SNR at 1.5T. Conclusion: Efficient bSSFP spiral in‐out provided high‐quality cardiac cine imaging and SNR recovery on a high‐performance 0.55T MRI system.